Industry and Plantation Collaboration: The Production of Chemical Fertilizer at CV Tabita Jaya and Its Chemical Compositions - Siburian, Rikson; Simanjuntak, Crystina; Tarigan, Kerista; Simatupang, Lisnawaty; Marrisa Purwati Sitinjak; Ruth Nia Magdalena Siburian; Theresia Octavia br Siburian, Claudia; Yosia Gopas Oetama Manik (Talenta Publisher, 2025)
This study aimed to formulate and evaluate an NPK compound fertilizer with a target ratio of 10:6:20 to enhance green mustard (Brassica juncea) productivity. At CV Tabita Jaya, standardized production methods were used to prepare the fertilizer by mixing Urea, triple superphosphate, and potassium chloride, with analytical confirmation of the nutrient content. Results showed nitrogen (N) content of 10.8%, phosphorus (P₂O₅) at 6.5%, and potassium (K₂O) at 20.8%, closely aligning with the target formulation. Moisture content was low at 2.48%, ensuring product stability and ease of application. Analytical techniques employed included Kjeldahl titrimetry for nitrogen, molybdate-vanadate spectrophotometry for phosphorus, and flame photometry for potassium. These methods demonstrated high reliability, with parameters such as repeatability, reproducibility, and recovery meeting international standards. The fertilizer is expected to support green mustard growth by enhancing critical metrics, including plant height, leaf number, and biomass accumulation. The study highlights the agronomic benefits of balanced NPK fertilization for green mustard, emphasizing enhanced nutrient absorption and sustainable agricultural practices. Furthermore, integrating this fertilizer with organic amendments may help mitigate potential soil degradation associated with prolonged use of inorganic fertilizers. The findings highlight the potential of precision-formulated fertilizers to enhance crop productivity while promoting environmental sustainability.